The effects of protein malnutrition on the pathogenesis of murine cytomegalovirus disease. - Teo, H. K. (1991)
BALB/c and CBA mice maintained on low (4%) or normal (18%) protein diets for 2 weeks after weaning were infected with a sublethal dose of murine cytomegalovirus, adjusted in proportion to body weight. Viral replication, histopathological changes and humoral responses to the virus were compared between the dietary groups 2-42 days post infection (p.i.). Higher numbers of viral antigen-positive cells and/or more prominent tissue necrosis were noted in the livers, spleens, hearts, adrenal glands, kidneys and bone marrows of infected protein-deficient mice. These mice also showed a delayed onset of leucocytic exudation in their livers and salivary glands, relative to infected mice on the normal diet. Second peaks of viral replication were detected by plaque assays in livers and spleens from protein-deficient mice and in livers from normal mice 12-18 days p.i., but few antigen-positive cells and no tissue necrosis were observed. Virus also persisted at higher titres in the salivary glands from protein-deficient mice. Although cellular immunity may be defective in these mice, humoral IgG and IgM responses to the virus were not inhibited. The influence of genetic factors on the pathogenesis of murine cytomegalovirus disease in protein-deficient mice is discussed.